LEARNING PHYSICS THROUGH COMICS MEDIA: AN ENHANCEMENT OF NEWTON LAW TOPICS ON ONLINE LEARNING - Syarif Eko Zahartian; Muhammad Junus; Nurul Fitriyah Sulaeman (ScienceEdu, 2022)
Comics are visual media to convey messages entertainingly so that they can be used in education and have become a tool that can promote the enjoyment of learning. This study aims to explore students' learning outcomes on Newton's Law material when using comic-based learning media. This study uses a quasi-experimental design method in the form of a non-equivalent control group design. The population in this study are all students of class X MIPA of SMAN 1 Muara Badak in the 2021/2022 academic year, where the sample used is class X MIPA 2 as the experimental class and class X MIPA 3 as the control class. The experimental class applies comic-based learning media, and the control class uses conventional learning media. The data were collected using pre-test and post-test and then analyzed using the n-gain and independent t-test analysis. This study has established that comic-based learning media is better than conventional learning media. The results showed a significantly different learning outcome between the experimental and the control classes with the acquisition of sig-2 tailed 0.000. In addition, the results of the assessment also showed an increase in student learning outcomes, seen from the results of the n-gain test, where the experimental class showed a higher accumulation of 0.3779 and entered the average category compared to the control class, which was only 0, 1090, which is in the low category. Based on these results, comics could be a supportive media to learn physics at the high school level.